(HOW) WILL AUTONOMOUS DRIVING INFLUENCE THE FUTURE SHAPE OF CITY LOGISTICS? - Mitrea, Oana; Kyamakya, Kyandoghere (Journal of Applied Engineering Science, 2017)
Many efforts have recently been done to partially or fully automate the driving process and make mobility more controllable and safe. In particular the full autonomous cars should free humans from the strains and dangers of driving while opening new possibilities for the experiencing of the daily life on the move. However, the importance of autonomous driving extends far beyond the mobility of persons (as drivers and passengers). Based on the review of the multidisciplinary literature about autonomous driving, the current contribution will generate hypotheses about the assessment and prediction of the impact of various autonomous driving use cases on city logistics’ problematic areas (mainly Last Mile and End-Consumer Movements).
Keywords: End-Consumer Movements (ECM); City Logistics; Automated Mobility on Demand; Autonomous Driving